An incidental finding of maternal multiple myeloma by non invasive prenatal testing. (28th November 2017) - Imbert‐Bouteille, Marion; Chiesa, Jean; Gaillard, Jean‐Baptiste; Dorvaux, Véronique; Altounian, Lucille; Gatinois, Vincent; Mousty, Eve; Finge, Sanae; Bourquard, Pascal; Vermeesch, Joris Robert; Legius, Eric; Vandenberghe, Peter
Abstract : What is already known about this subject? Non invasive prenatal testing for fetal trisomies 13, 18, and 21 occasionally identifies maternal cancer. What does this study add? A further case of maternal cancer incidentally diagnosed by routine NIPT. Extensive NIPT abnormalities are unlikely to be of fetal origin. Information given to patients should also adequately advise patients on potential incidental findings and might offer the option to opt out of receiving results beyond the trisomy report. International guidelines would improve patient counseling.